Pediatric Liver Transplantation: A Clinical Review - J. S. Simi Mohan (Recent Developments in Medicine and Medical Research Vol. 3, 2021)
Liver transplantation is an accepted therapy for end stage liver disease and fulminant hepatic failure. It has significantly improved the prognosis in patients with End Stage Liver Disease. This clinical review describes the pediatric liver transplantation and its associated therapy. Living organ donation is a complex decision for the donor and his or her family. An ideal donor should be mentally, physically and psychologically fit. The aim of donor evaluation is to find out whether donor is suitable for donation or not, as well as detect hidden medical diseases in him or her. It provides a ray of hope to the child and family and opportunity to live a long and healthy life.